DEVELOPMENT OF PREDICTIVE EQUATIONS FOR PERMEABILITY AND STRENGTH OF OIL WELL CEMENT USING ELECTRICAL IMPEDANCE - RIDHA, SYAHRIR (2012)
Oilwell cement plays an important role either to seal-off the casing or to isolate the formation layers from the fluids infiltration that might cause a well bore damage. A cautious evaluation of cement after displacement is coming to be crucial to secure the long-term durability and integrity of wellbore. This work in turn is focused on the utilization of electrical properties for predicting the permeability and compressive strength of oil well cement. At present work, an electrical impedance measurement has been used to detect the conductivity evolution of oil well cement during early hydration. It was then followed by an examination towards the potential existence of interface conductivity along with its effects on various water cement ratios, curing temperature and also pressure. In analyzing the interface conductivity, the evaluation of the electrical responses in the form of conductivity dispersion characteristics has been done. Together with porosity data, conductivity data consisting of bulk and pore solution conductivity were examined to study several composite conductivity models to describe certain changes in the electrical conductivity of oil well cement system. Several empirical equations for predicting the permeability and compressive strength of oilwell cement based on its electrical properties response have been proposed. To validate the result, the proposed equations were experimentally compared to other cement samples with different water cement ratios and curing conditions. A comparison has also been made to the equation proposed by KatzThompson and Johnson's and also data from literatures. A good agreement between the proposed equation and measured data then shows that it is feasible to obtain the cement's strength and permeability in place using these electrical properties. Permeability and compressive strength in mature stage, furthermore, can be predicted by the proposed equations.